The Impact of Perceived Ease of Use and Perceived Risk of PayLater on Impulse Buying Behavior among Shopee Consumers - Khansa Puti Zharifah Muza; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study explores how Shopee PayLater users' perceptions regarding the usability and potential risks of BNPL to their impulse buying behavior. A quantitative research design was applied using a survey approach, in which data were collected through questionnaires distributed to Shopee PayLater users. The analysis was carried out with SPSS, revealing that Perceived Ease of Use plays an important role on impulse buying behavior. This means that when Shopee PayLater is easy to understand and use, the consumers are more likely to make purchases without prior planning. In addition, Perceived Risk also has a significant effect on impulse buying behavior. This finding indicates that perceived risk does not always prevent consumers from making impulsive purchases in a buy now, pay later system. Overall, the findings confirm that Perceived Ease of Use together with Perceived Risk affect impulse buying behavior. This suggests that impulse buying among Shopee PayLater users is influenced by both the simplicity of the payment system and consumers’ perceptions of risk